Family Behavior Model with Amount Cases in Odgj Case Study in Parringan Jenangan Village, Ponorogo - Eky Okviana Armyati vivi; Nurul Sri Wahyuni; Dwi Nurwulan Pravitasari; Dian Laila Purwoningrum (Universitas Muhammadiyah Malang, 2023)
Family is a primary group consisting of two or more people who have a network of interpersonal interactions, blood relations, marital relations, and adoption. (kependudukan.co.id). Role of Families with ODGJ Based on the causes of mental disorders, patients who experience mental disorders need the role of various parties for the healing process, including psychiatrists who can provide psychopharmacology, clinical psychologists who can provide psychoeducation and psychotherapy, health cadres who can monitor the patient's condition and helping the patient's family to refer to a health facility. When they see people with mental disorders going berserk, what they do is most do is scream for help, 83% of people scream when disturbed by ODGJ. Apart from that, when there is an ODGJ going berserk, the most important thing the community does is ask for help from other people, 60% of people choose to ask others for help when they are disturbed by ODGJ. Of the 30 people who were asked what they did when ODGJ went berserk. What they usually do is call the health worker or seek help from others.